Kelimpahan plankton Prorocentrum sp. pada tambak intensif udang vaname (Litopenaeus vannamei) - Heri Ariadi; M.B. Syakirin; Tri Yusufi Mardiana; Hayati Soeprapto; Linayati Linayati; Benny Diah Madusari (Fakultas Pertanian Universitas Yudharta Pasuruan, 2023)
Introduction: Prorocentrum sp. is one of the harmful algae genera that often grows in the aquatic ecosystems of vaname shrimp (L. vannamei) ponds. The purpose of this study was to determine the abundance and dynamics of the Prorocentrum sp. during the shrimp culture period of vaname shrimp (L. vannamei) in intensive ponds. Method: This research was conducted on 4 ponds with a size of 3,200 m2 and a stocking density of 120 fish/m2. The research variables observed were water quality parameters and Prorocentrum sp. which is carried out every 7 days during the shrimp cultivation periods. Result: Based on the results of study, the water quality parameters during the shrimp culture period tend to be stable, except for the water pH parameters which have relatively high afternoon pH fluctuations. Prorocentrum sp. genera during the shrimp culture period, the plankton genus was the most dominant compared to other genera of the Dinoflagellate class. The dynamics of the Prorocentrum sp. abundance on the intensive pond, there was a significant correlation between the solubility of TAN (Total Ammonia Nitrogen) content of 74.8% and the water temperature of 83.3%. Conclusion: The abundance dynamics of Prorocentrum sp. genera during aquaculture period of vaname shrimp (L. vannamei) fluctuated dynamically following the solubility trend of TAN (Total Ammonia Nitrogen) levels and water temperature flux in the pond ecosystem